Development of an NMR microprobe procedure for high‐throughput environmental metabolomics of Daphnia magna. (17th April 2015) - Nagato, Edward G.; Lankadurai, Brian P.; Soong, Ronald; Simpson, André J.; Simpson, Myrna J.; Simpson, Andre J.
<x xml:space="preserve">Abstract</x> Nuclear magnetic resonance (NMR) is the primary platform used in high‐throughput environmental metabolomics studies because its non‐selectivity is well suited for non‐targeted approaches. However, standard NMR probes may limit the use of NMR‐based metabolomics for tiny organisms because of the sample volumes required for routine metabolic profiling. Because of this, keystone ecological species, such as the water flea Daphnia magna, are not commonly studied because of the analytical challenges associated with NMR‐based approaches. Here, the use of a 1.7‐mm NMR microprobe in analyzing tissue extracts from D. magna is tested. Three different extraction procedures (D2O‐based buffer, Bligh and Dyer, and acetonitrile : methanol : water) were compared in terms of the yields and breadth of polar metabolites. The D2O buffer extraction yielded the most metabolites and resulted in the best reproducibility. Varying amounts of D. magna dry mass were extracted to optimize metabolite isolation from D. magna tissues. A ratio of 1–1.5‐mg dry mass to 40 µl of extraction solvent provided excellent signal‐to‐noise and spectral resolution using 1H NMR. The metabolite profile of a single daphnid was also investigated (approximately 0.2 mg). However, the signal‐to‐noise of the 1H NMR was considerably lower, and while feasible for select applications would likely not be appropriate for high‐throughput NMR‐based metabolomics. Two‐dimensional NMR experiments on D. magna extracts were also performed using the 1.7‐mm NMR probe to confirm 1H NMR metabolite assignments. This study provides an NMR‐based analytical framework for future metabolomics studies that use D. magna in ecological and ecotoxicity studies. Copyright © 2015 John Wiley & Sons, Ltd.